Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1016/0014-5793(89)80578-2
|View full text |Cite
|
Sign up to set email alerts
|

Photolabeled tryptic degradation products of benzodiazepine‐binding proteins are glycopeptides Implications for localization of cleavage sites

Abstract: Crude synaptic membranes of avian and mammalian brain tissue were photolabeled with the benzodiazepine-receptor ligand PH]flunitrazepam and subsequently treated extensively with trypsin followed by incubation with endoglycosidase F. SDS-polyacrylamide gel electrophoresis and fluorography revealed that the final tryptic degradation product of 25 kDa in both pigeon and calf brain is deglycosylated in two steps. These results were confirmed by immunoblots of similarly pretreated membranes of pig brain using the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To date, site-directed mutagenesis has identified the amino acids Gly 225 of the ␣ 1 subunit (6), His 101 of the ␣ 1 subunit (7), and Thr 142 of the ␥ 2 subunit (8) as residues that play a role in conferring the differential binding affinities of benzodiazepine ligands for the GABA A receptor. Biochemical approaches have shown that the site of photoaffinity labeling by the classical agonist, [ 3 H]flunitrazepam, is associated with the ␣ subunit of the GABA A receptor (9,10) within the large extracellular amino-terminal domain (11,12). In addition, partial sequences of proteolytic fragments from photoaffinity labeled receptors have indicated that the [ 3 H]flunitrazepam site occurs within amino acid residues 8 -297 of the ␣ 1 subunit (13), and using subunit specific antibodies, the site has been predicted to occur within residues 59 -158 of the ␣ 1 sequence (14).…”
mentioning
confidence: 99%
“…To date, site-directed mutagenesis has identified the amino acids Gly 225 of the ␣ 1 subunit (6), His 101 of the ␣ 1 subunit (7), and Thr 142 of the ␥ 2 subunit (8) as residues that play a role in conferring the differential binding affinities of benzodiazepine ligands for the GABA A receptor. Biochemical approaches have shown that the site of photoaffinity labeling by the classical agonist, [ 3 H]flunitrazepam, is associated with the ␣ subunit of the GABA A receptor (9,10) within the large extracellular amino-terminal domain (11,12). In addition, partial sequences of proteolytic fragments from photoaffinity labeled receptors have indicated that the [ 3 H]flunitrazepam site occurs within amino acid residues 8 -297 of the ␣ 1 subunit (13), and using subunit specific antibodies, the site has been predicted to occur within residues 59 -158 of the ␣ 1 sequence (14).…”
mentioning
confidence: 99%
“…It is an oligomeric protein complex of which several subunits have been cloned (Schofield et al, 1987;Levitan et al, 1988;Pritchett et al, 1988;Khrestchatisky et al, 1989;Lolait et al, 1989;Shivers et al, 1989;Ymer et al, 1989a,b;Liiddens et al, 1990;Malherbe et al, 1990). Immunological evidence indicates that benzodiazepine binding sites are located on the a-subtypes (Schoch et al, 1985;Fuchs et al, 1988Fuchs et al, , 1990Schmitz et al, 1988Schmitz et al, , 1989, although P-subunits are also implicated (Bureau and OLsen, 1988).…”
mentioning
confidence: 99%